Android-Based Geolocation Technology on a Blood Donation System (BDS) Using the Dijkstra Algorithm - Syaiful Ahdan; Setiawansyah Setiawansyah (IJAIT (International Journal of Applied Information Technology), 2021)
Blood transfusion is an activity that is often carried out in order to save human life. The availability of appropriate bloodstock is crucial for use during special medical conditions. Therefore, the blood collection center must ensure availability; therefore, it needs to recruit active blood donors, difficult patients to find blood stocks, which will be discussed in this study. The contribution of this research is to design an information system that can find blood donors in the Bandar Lampung area with geolocation technology and use the Dijkstra algorithm to determine the closest route, with a system developed on the Android platform. The system can recommend donors to patients who need blood according to the patient's qualifications. Results obtained are an android-based mobile application that can search for geolocation-based blood donors using the Dijkstra algorithm, which can map the location of the nearest blood donor based on the patient's location. Based on data obtained from the results of system testing on functionality and usability, the system can map the location of blood donors and provide blood donor recommendations for patients in need. System testing is carried out using the ISO 9126 standard using the usability aspect, which consists of four test characteristics: the understanding aspect, the learning aspect, the ability aspect, and the operability aspect, and the attractiveness aspect.